Reducing Ex-offender Health Disparities through the Affordable Care Act: Fostering Improved Health Care Access and Linkages to Integrated Care - Ejike-King, Lacreisha (AIMS Public Health, 2014)
Despite steadily declining incarceration rates overall, racial and ethnic minorities, namely African Americans, Latinos, and American Indians and Alaska Natives, continue to be disproportionately represented in the justice system. Ex-offenders commonly reenter communities with pressing health conditions but encounter obstacles to accessing care and remaining in care. The lack of health insurance coverage and medical treatment emerge as the some of the most reported reentry health needs and may contribute to observed health disparities. Linking ex-offenders to care and services upon release increases the likelihood that they will remain in care and practice successful disease management. The Affordable Care Act (ACA) offers opportunities to address health disparities experienced by the reentry population that places them at risk for negative health outcomes and recidivism. Coordinated efforts to link ex-offenders with these newly available opportunities may result in a trajectory for positive health and overall well-being as they reintegrate into society.